Lack of rebound during intermittent transdermal treatment with glyceryl trinitrate in patients with stable angina on background beta blocker. Issue 3 (March 1993) - Holdright, D R; Katz, R J; Wright, C A; Sparrow, J L; Sullivan, A K; Cunningham, A D; Fox, K M
Abstract : OBJECTIVE–To assess whether intermittent transdermal treatment with glyceryl trinitrate causes clinically significant rebound in patients maintained on beta blockers for stable angina pectoris. DESIGN–Serial treadmill exercise testing in a double blind, randomised, placebo controlled cross over trial. Baseline exercise testing was performed at 0900 and 1100 at visit 1. Transdermal glyceryl trinitrate patches releasing 15 mg/24 h were applied at 2200 the evening before visits 2 and 3, and exercise testing was performed at 0900 the next morning. The patch was removed and replaced with either an identical patch or matching placebo and exercise tests were repeated two hours later. The alternative treatment was given at visit 3. SETTING–Tertiary referral centre. PATIENTS–14 patients with stable angina pectoris maintained on beta blocker treatment alone. MAIN OUTCOME MEASURES–Time to angina, 1 mm ST segment depression, and total time, together with heart rate, systolic blood pressure, and rate-pressure product. RESULTS–Active treatment improved treadmill performance at 0900 and 1100. Time to angina, time to 1 mm ST segment depression, and total time fell significantly on placebo compared with the 0900 exercise test on active treatment, but were not significantly different to the baseline exercise test either. CONCLUSIONS–Intermittent transdermal treatment with glyceryl trinitrate is not associated with the rebound phenomenon in patients maintained on beta blockers for stable angina pectoris.